GO BUMDES BERJAYA (Gerakan Membangun Operasional Badan Usaha Milik Desa yang Berdikari Sejahtera dan Melayani) - Moh. Rizky Godjali; Ika Arinia Indriyany (Komunitas : Jurnal Pengabdian Kepada Masyarakat, 2021)
Village-Owned Enterprises (BUMDES) are a breakthrough in advancing villages and improving the welfare of their citizens through a business unit scheme. In fact, BUMDES can be used as a means of boosting the economy of rural people. However, various problems have hindered the ideal management of BUMDES and provided benefits for the village and its citizens. This Community Service Program is designed to provide an effort to improve the non-ideal condition of BUMDES in order to become Berjaya (Berdikari Sejahtera Melayani). This program focuses on building operations or pioneering BUMDES which is still not being carried out seriously in many villages in Banten Province. The selected partner villages were identified as having three main problems, namely weak institutional governance as a business entity, and not yet in the form of a legal entity. Second, the lack of types/business products and not optimal profits from the sale of business products. In addition, there is also no identification of new products based on local advantages that involve broad participation from the community. Third, there is no village asset management and good financial management. This problem can be overcome by implementing 3 (three) main programs for structuring the organization and activities of BUMDES, namely Institutional Strengthening of Business Entities registered as Legal Entities; Identification of key products and businesses based on local advantages; and Formulation of Village Asset and Financial Management Strategies. This program can be implemented by using a stimulus method approach in the form of Counseling and Training-based Guidance, as well as practical assistance/simulation to overcome all priority issues.